Single dose antibiotic prophylaxis for prevention of surgical site infection in elective surgery - Borade, Swaroop V.; Syed, Obaid (International Surgery Journal, 2017)
Background: Surgical site infections are associated with prolonged hospital stays and increased costs. Infection develops when endogenous flora is translocated to a normally sterile site. Seeding of the operative site from a distant site of infection can also occur (especially in patients with prosthesis or another implant). Factors influencing the development of surgical site infections include bacterial inoculums and virulence, host defences, preoperative care and intraoperative management. Hence there is the need for antibiotic prophylaxis to overcome this problem. This study was planned to evaluate the effect of prophylactic antibiotic in clean and clean contaminated cases and to assess the outcome. Methods: A prospective study was conducted which include 100 patients undergoing elective surgery admitted to the department of general surgery IIMSR’s Medical College and Hospital, Warudi, Jalna, relevant information of each patient was collected according to the Performa designed for the study. Cefuroxime was used preoperatively 30 min prior to incision and its impact on postoperative wound infection was studied. Results: We had 100 cases in our study predominantly males with maximum individuals in 31-40 years age group, we had 67% clean and 33% clean contaminated surgeries done and had 3% case of superficial surgical site infection. Conclusions: A single preoperative dose of antibiotic Cefuroxime is effective to prevent surgical site infection in elective case assuming an uncomplicated procedure.